Identifikasi Jamur Rizosfer Tomat (Solanum lycopersicum L.) di Desa Buahan dan Pinggan, Kecamatan Kintamani - Ida Isnawati; Srie Marhaeni Julyasih; Yuliastuti Yuliastuti (Program Studi Pendidikan Biologi, 2026)
The importance of the agricultural sector, especially tomato cultivation in the Kintamani region related to plant health and crop productivity. The decline in tomato production is suspected to be related to fungal pathogen attacks in the rhizosphere that affect plant health. The objective of this study was to identify the types of rhizosphere fungi present in two tomato plantation locations and to determine the relationship between the types of fungi and agricultural practices in each location. The research method was descriptive exploratory with systematic soil sampling at two different locations, followed by isolation and identification in the laboratory. The results showed that there were three genera of rhizosphere fungi at each research location identified in Buahan Village, including the genera Aspergillus, Penicillium, and Trichoderma, while in Pinggan Village, the genera Aspergillus, Penicillium, and Fusarium were found. In general, Penicillium was the most dominant genus at both research locations. While Pinggan Village was dominated by Fusarium, a pathogen that is harmful to plants, and the absence of Trichoderma. This difference is closely related to differences in agriculture practices such as fertilizer application and the use of chemical pesticides. The conclusion states that the pattern of rhizosphere fungal dominance is greatly influenced by soil management systems, which have an impact on rhizosphere health and tomato productivity. These findings provide an important scientific basis for the development of more environmentally friendly and sustainable tomato farm management strategies.